Diet-induced hyperhomocysteinemia causes sex-dependent deficiencies in offspring musculature and brain function - Suszyńska-Zajczyk, Joanna; Witucki, Łukasz; Perła-Kaján, Joanna; Jakubowski, Hieronim (Frontiers in Cell and Developmental Biology, 2024)
Hyperhomocysteinemia (HHcy), characterized by elevated homocysteine (Hcy) levels, is a known risk factor for cardiovascular, renal, and neurological diseases, as well as pregnancy complications. Our study aimed to investigate whether HHcy induced by a high-methionine (high-Met) diet exacerbates cognitive and behavioral deficits in offspring and leads to other breeding problems. Dietary HHcy was induced four weeks before mating and continued throughout gestation and post-delivery. A battery of behavioral tests was conducted on offspring between postnatal days (PND) 5 and 30 to assess motor function/activity and cognition. Results were correlated with brain morphometric measurements and quantitative analysis of mTOR/autophagy markers. The high-Met diet significantly increased parental and offspring urinary tHcy levels and influenced offspring behavior in a sex-dependent manner. Female offspring exhibited impaired cognition, potentially related to morphometric changes observed exclusively in HHcy females. Male HHcy pups demonstrated muscle weakness, evidenced by slower surface righting, reduced HLS hanging time, weaker grip strength, and decreased activity in the beaker test. Western blot analyses indicated downregulation of autophagy and upregulation of mTOR activity in HHcy cortexes. HHcy also led to breeding impairments, including reduced breeding rate, in-utero fetal death, lower pups’ body weight, and increased mortality, likely attributed to placental dysfunction associated with HHcy. In conclusion, a high-Met diet impairs memory and cognition in female juveniles and weakens muscle strength in male pups. These effects may stem from abnormal placental function affecting early neurogenesis, dysregulation of autophagy-related pathways in the cortex, or epigenetic mechanisms of gene regulation triggered by HHcy during embryonic development.